He ipu whakairo-- inscribing peace, knowledge and understanding : new/beginning social science teachers' delivery of Treaty of Waitangi and citizenship education in New Zealand secondary schools : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Māori Studies at Massey University, Palmerston North, Aotearoa New Zealand - Black, Hona (Massey University, 2013)
This thesis examines new/beginning social science teachers’ delivery of Treaty of Waitangi and citizenship education in New Zealand secondary schools. A lack of education about the Treaty and New Zealand citizenship has seen poor understanding amongst our citizenry about the Treaty, race and ethnicity in Aotearoa New Zealand. Research conducted with six new/beginning Maori and non-Maori social science teachers explored, from their perspective, their ability to deliver Treaty and citizenship education based on their teacher training, the New Zealand Curriculum, teaching resources, and their professional development. Moteatea and whakatauaki, critical consciousness and critical education formed a theoretical base for this work. Individual semi-structured in-depth interviews and thematic analysis were utilized to collect and analyse data, observing Durie’s (1998) ethical framework on ‘mana’. Research findings revealed that Treaty education receives little attention in schools, and teachers, little support to deliver it. For example, although specified within the Curriculum as a learning subject as well as a principle for schools, teachers reported they received no guidance on how to deliver education on the Treaty and were unable to identify how it translated into classroom or school-wide practices. He ipu whakairo, a ‘vessel to be carved’, emphasises the inscribing of peace, new knowledge and understanding in our society that is to be had from a renewed emphasis on Treaty of Waitangi and citizenship education in our secondary schools. From new/beginning teachers’ aspirations for greater support in their Treaty and citizenship teaching, the recommendations from this research provide a solid platform for future development in this area.
Keywords: Treaty of Waitangi; Citizenship; Study and teaching (Secondary); Secondary schools; New Zealand